Teias de caridade e o lugar social dos expostos da Freguesia de Nª Srª da Apresentação: capitania do Rio Grande do Norte, século XVIII - Paula, Thiago do Nascimento Torres de (2009)
The abandonment of newborn children is a reality nowadays. This reality enables us to discuss this issue in other temporalities, in all kinds of societies. Thus, this work aims to demonstrate how the population that lived at Freguesia de Nossa Senhora da Apresentação, a civil parish at a Rio Grande do Norte captaincy, socially placed the abandoned newborn during in the eighteenth century. These newborn were called exposed ones at the time and were inserted in a regional Exposed Circle. The research also discussed how the local Council assembly sheltered these newborn. For research development the following manuscript documents were used: baptism, wedding and demise documents at Freguesia de Nossa Senhora da Apresentação as well as the first Book of Records if the matrix church at this civil parish. The research also considered the terms of the Council assembly. Some printed documents were used such as Philippine Ordainments, the First Constitutions of the Archbishop in 1707 including the Lunario contents as well as texts from André João Antonil and Henry Koster. In the analysis reference work related to Social History was used. Thus, it is possible confirm that there was construction of socially accepted places for these exposed on behalf of the colonist at the region